Analisis Penyediaan Air Bersih Di FKIP (Fakultas Keguruan dan Ilmu Pendidikan) Universitas Tanjungpura Pontianak - Sutopo, Suryo; Umar, Umar; Gunarto, Danang (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Until now, the level of efficiency has not been analyzed for the provision of clean water in the area of the Faculty of Teacher Training and Education, Tanjungpura University, Pontianak. The need for clean water has increased every year because the needs issued to each person at the Faculty of Teacher Training and Education, University of Tanjungpura Pontianak are not certain. Therefore, it is very important to analyze whether the availability of water in each building of the Teaching and Education Faculty of Tanjungpura Pontianak University can still be fulfilled because from time to time there will always be changes in the amount of clean water used. In the final project, it is predicted that the need for clean water for the Teaching and Education Faculty of Tanjungpura University Pontianak in 2023 is also taken, and data is taken on the use of clean water for one month working days from March to April 2023. Observations on 3 meters in the Education Area Faculty of Teacher Training and Education, University of Tanjungpura, Pontianak, that the amount of clean water used is 90.37 m3/month. Then an analysis of the need for clean water was carried out in the Teaching and Education Faculty of Tanjungpura Pontianak University, both in the building sector and the total users of clean water in the area. The total users of clean water is 541.6. The results of the study found that the effectiveness of each zone was different, the amount of clean water used was less than the predicted amount of water needed, so it could be concluded that the provision of clean water at the Teaching and Education Faculty of Tanjungpura University in 2023 was not effective.